Rancangan Bangun Sistem Monitoring Suhu Berbasis Internet of Things di Masjid Mudhi Ali Al-Sulthon - Musyaffa, Arkan Ari; Saludin, Saludin (Jurnal Sosial Teknologi, 2025)
As a place of worship for Muslims, a mosque is a public space used by many worshippers simultaneously. To maintain the comfort and health of worshippers, especially during extreme heat, a system capable of making automatic decisions based on real-time room temperature and humidity conditions is required. This research developed an automated Internet of Things (IoT)-based system integrated with Firebase and a Laravel-based web application. This system is designed to automatically control fans: the fans will turn on when the temperature is high and turn off when the temperature returns to normal or becomes too cold. Temperature and humidity sensors are placed at strategic points within the mosque to collect environmental data. This data is then sent in real time to Firebase and displayed on a web dashboard. The system will send notifications to the mosque management via the web dashboard and Gmail notifications if the temperature or humidity exceeds predetermined normal limits. Notifications include information on the date, day, temperature, humidity, and recommended actions. Based on this data, the system can also automatically make decisions about turning fans on or off to maintain room comfort.